A triple-stimuli responsive hormone delivery system equipped with pillararene magnetic nanovalves. (9th November 2018) - Li, Xiangshuai; Han, Junyou; Wang, Xin; Zhang, Yanxin; Jia, Chengguo; Qin, Jianchun; Wang, Chunyu; Wu, Jia-Rui; Fang, Wenhui; Yang, Ying-Wei
Abstract : A stimuli responsive hormone delivery system was designed and constructed from mesoporous silica and pillararene magnetic nanovalves, which can release hormones on command to promote the growth of Arabidopsis thaliana and cabbage. Abstract : Nanotechnology in agriculture and food industry has attracted significant attention over the past few decades. Benefiting from the introduction of controlled release capability, drug/cargo delivery systems possess great advantages for plants in delivering plant genes, hormones, pesticides, and fertilizers to mediate their growth. Herein, we construct a new smart multi-stimuli responsive hormone delivery system to regulate the release of gibberellin acid (GA3) for plant growth. Hollow mesoporous silica nanoparticles have been utilized as nanocarriers, upon which water soluble carboxylatopillar[5]arene ammonium (WP[5]A) functionalized Fe3 O4 nanoparticles (WP[5]A-Fe3 O4 ) are installed as nanovalves via host–guest interactions (WP[5]A-Fe3 O4 capped HMSNs are denoted as HMSN/Fe3 O4 ). Bidirectional pH-responsive supramolecular nanovalves have been constructed for the first time, and under acidic or alkaline conditions hormones can be released out from GA3-loaded HMSN/Fe3 O4 (GA3-HMSN/Fe3 O4 ) to promote the growth of plants. Interestingly, the GA3-HMSN/Fe3 O4 nanoparticles can also respond to other stimuli including 1, 4-butanediamine (BDA) and ultrasound. This smart delivery system has been successfully applied in plants like Arabidopsis thaliana ( A. thaliana ) and cabbages, and our experimental results suggested that the GA3-HMSN/Fe3 O4 hybrid nanomaterials can obviously promote the growth of both plants. Therefore, we envision that this magnetic multi-stimuli responsive system will hopefully play an important role in promoting agricultural industry development.